A Scientometric Analysis of Audit Quality Studies Using VOSviewer - Judijanto, Loso; Susanto, Edy (West Science Accounting and Finance, 2025)
This study presents a scientometric analysis of global audit quality research published between 2000 and 2025, employing VOSviewer to visualize and interpret the intellectual and thematic structure of the field. Using bibliographic data from the Scopus database, the study explores co-authorship networks, keyword co-occurrence, country collaborations, and temporal trends. The results reveal a strong concentration of research in developed economies, particularly the United States, Australia, and Germany, while emerging economies are gradually entering the discourse through international collaboration. Core research themes include audit fees, auditor independence, corporate governance, and earnings management, while recent developments highlight the growing relevance of artificial intelligence, corporate social responsibility, and key audit matters. The temporal and density visualizations indicate a shift from traditional audit concerns to more strategic, ethical, and technological dimensions. This study offers a comprehensive roadmap for future research, supporting scholars, practitioners, and policymakers in navigating and expanding the audit quality knowledge base.